Analysis on Education Provision Policy in Frontier, Outermost, and Underdeveloped Regions to Improve National Security in Sebatik Island, Indonesia - Asri Nur Aina; Siswidyanto Siswidyanto; Ainul Hayat (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, Indonesia, 2021)
This article aimed to analyze the Government Policy in the process of implementing education to improve National Security at the Sebatik Island of Nunukan Regency. The author analyzed using Bardach’s Eightfold path to more effective problem solving which consists of defining the problem, assembling the evidence, constructing the alternatives, selecting the criteria, projecting the outcomes, confronting the trade-offs, deciding, and telling the story. This is a descriptive-type study with a qualitative approach. Study results shows that in Nunukan Regency, especially Sebatik Island that is considered as a Frontier, Outermost, and Underdeveloped region, which also lies at the border between Malaysia and Indonesia—haven’t been optimally carrying out policies on education implementation for improving national security. This was also proven by the number of schools that lack the necessary facilities and infrastructures, in addition to the curriculum that has yet to instil national security strengthening in schools and the lack of routine for nationalism-related activities given by the local government. Therefore, the local government should synergize with other parties, such as the Indonesian Army and education communities to improve national security in Sebatik Island while also strengthen the students’ sense of nationalism through accommodating school subjects on Indonesian nationality and culture.